The complete mitochondrial genome of Kaloula rugifera (Amphibia, Anura, Microhylidae). (2nd September 2016) - Deng, Xuyan; Wang, Shouhong; Liang, Xixi; Jiang, Jianping; Wang, Bin; Deng, Liangji
Abstract: We determined the complete mitochondrial genome of Kaloula rugifera in this work. The mitogenome was 17, 073 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region (D-loop). The base composition of the light strand was 29.7% A, 30.4% T, 25.7% C and 14.2% G. The gene order and contents of it is identical to most amphibian mitogenome. All protein-coding genes began with ATG as start codon except ND1 gene beginning with GTG and COI gene beginning with ATA. Five protein-coding genes ( COII, ATP 6, COIII, ND3 and ND4 ) ended with incomplete stop codon T. The 22 tRNA genes with the size ranging from 65 bp to 73 bp were interspersed along the whole genome. The D-loop region containing tandem repetition was 1675 bp in length and heavily biased to A + T nucleotides.